2018
DOI: 10.1097/md.0000000000012449
|View full text |Cite
|
Sign up to set email alerts
|

Viabahn stent graft compared with prosthetic surgical above-knee bypass in treatment of superficial femoral artery disease

Abstract: The prosthetic surgical above-knee bypass (pAKB) is a standard therapy in superficial femoral artery (SFA) occlusive disease in absence of suitable vein. Viabahn graft has been established as a promising alternative. Since limited comparative data are available, we conducted a retrospective study to compare long-term outcomes of these 2 therapies in a real-world setting.Records of 52 patients (60 limbs), who were treated by pAKB (29 limbs) or Viabahn (31 limbs) were reviewed. Patients were followed up by clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Data from observational studies indicate a higher rate of technical success with the use of alternative access such as distal superficial femoral has an impact on MALE; however, these were observational studies with limited ability to derive definitive conclusions. 28 In keeping with previous findings, 16,21,29 Furthermore, the inclusion and exclusion criteria of individual trials differed slightly. Such differences were accounted for by adjusting outcomes for differences for these factors.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 66%
See 1 more Smart Citation
“…Data from observational studies indicate a higher rate of technical success with the use of alternative access such as distal superficial femoral has an impact on MALE; however, these were observational studies with limited ability to derive definitive conclusions. 28 In keeping with previous findings, 16,21,29 Furthermore, the inclusion and exclusion criteria of individual trials differed slightly. Such differences were accounted for by adjusting outcomes for differences for these factors.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 66%
“…Whereas the individual randomized controlled trials were too small to derive definitive conclusions on the effect of the different treatment strategies on these clinical endpoints, observational studies with larger sample sizes have shown mixed results. 17,[18][19][20][21][22][23] To date, this analysis is the most robust evidence on the comparison of EVT with stent implantation vs BSx for these clinical endpoints.…”
Section: Femoropopliteal Artery Revascularizationmentioning
confidence: 97%